Находка садовой сони (Eliomys quercinus L., 1776) на Украине - Гиренко, Л.Л.; Литвиненко, Е.Ф. (Вестник зоологии, 1971)
There are no data in the literature concerning the distribution of Eliomys querci- *nus L. in the territory of the Ukraine confirmed by actual collection materials. That is why in recent researches (Korneev, 1952, 1965) this species was excluded from the composition of mammals fauna in the Ukrainian SSR. On April 25, 1965, Eliomys quercinus L. ( ad) was found for the first time within the boundaries of the Ukraine the outskirts of the village Velranovka (Uman district. Cherkassy region).